Distribution of Hermann’s tortoise across Serbia with implications for conservation - Golubović, Ana; Tomović, Ljiljana; Nikolić, Marko; Nikolić, Sonja; Anđelković, Marko; Arsovski, Dragan; Iković, Vuk; Gvozdenović, Slađana; Popović, Miloš (Archives of Biological Sciences, 2019)
Paper description: The Hermann’s tortoise and its habitats are among conservation priorities in the European Union. Populations of western subspecies are closely monitored and basic information about eastern subspecies is just starting to emerge. We used precise observation data to model the distribution of Hermann’s tortoise in Serbia and its ecological niche. Both modeled and observed distributions suggest that most suitable habitats are situated in lowland areas of eastern, central and southern Serbia, under semi-open habitats ranging from pastures and shrubs to broad leaf forests. Our results provide crucial information which should be considered when shaping NATURA 2000 sites in Serbia. Abstract: Hermann’s tortoise (Testudo hermanni) is among the conservation priorities in the European Union. Consequently, it is included in Annexes II and IV of the EU Habitats Directive, Annex II of the Bern Convention, and Annex II of the CITES Convention. Hermann’s tortoise conservation programs compile insights on the threats affecting population viability, along with factors shaping the species’ distribution. Serbian populations of the eastern subspecies (Testudo hermanni boettgeri) seem numerous and therefore prosperous, but recent population viability analyses revealed that they are susceptible to rapid demographic changes and/or habitat destruction. This implies the need for effective population monitoring and protection, as well as mapping and conservation of suitable habitats. In this paper we summarized current knowledge about the geographic distribution of Hermann’s tortoise in Serbia and modeled its ecological niche. Our results corroborate and uphold the known species’ distribution in Serbia. Most suitable habitats are situated in the lowland areas of eastern, central and southern Serbia, under semi-open habitats, such as pastures and shrubs, broadleaf forests, and all successional stages in between. The results provided in this paper should be considered in the selection and shaping of NATURA 2000 sites in Serbia. https://doi.org/10.2298/ABS190406034G Received: April 6, 2019; Revised: May 1, 2019; Accepted: May 7, 2019; Published online: June 5, 2019 How to cite this article: Golubović A, Tomović Lj, Nikolić M, Nikolić S, Anđelković M, Arsovski D, Iković V, Gvozdenović S, Popović M. Distribution of Hermann’s tortoise across Serbia with implications for conservation. Arch Biol Sci. 2019;71(3):509-16.